Cancer treatment model with the Caputo-Fabrizio fractional derivative - Dokuyucu, Mustafa Ali; Celik, Ercan; Bulut, Hasan; Baskonus, Haci Mehmet (Springer Heidelberg, 2018)
In this article, a model for cancer treatment is examined. The model is integrated into the Caputo-Fabrizio fractional derivative first, to examine the existence of the solution. Then, the uniqueness of the solution is investigated and we identified under which conditions the model provides a unique solution.